A Feedback Integrated Web-Based Multi-Criteria Group Decision Support Model for Contractor Selection using Fuzzy Analytic Hierarchy Process - Afolayan, Abimbola Helen; Ojokoh, Bolanle Adefowoke; Adetunmbi, Adebayo (arXiv.org, 2021)
In this paper, a feedback integrated multi-criteria group decision support model for contractor selection was proposed.